Investigating Students’ Multimodal Literacy on Prose in Language Education Course at Billfath University - Rahmah, Anita; Fitriyana, Eka (Universitas Islam Lamongan, 2024)
This research aims to investigate multimodal literacy on Prose in Language Education course at Billfath University, focusing on how students understand and create meaning through text, images, sound, and digital media. Using qualitative methods, data from 20 sixth-semester students (academic year 2023/2024) were collected through observations, interviews, surveys, and document analysis. Findings indicate the integration of multimodal literacy in activities such as creative writing and digital application use. Students effectively applied multimodal literacy in tasks such as text analysis and digital presentations, despite challenges like limited technology access and technical skills. The research recommends continuous integration of multimodal literacy into the English language curriculum to enhance students' language skills.